Is the asylum partnership between the UK and Rwanda compliant with international refugee and human rights law, specifically the principle of non-refoulement, the principle of non-penalization of irregular entry by refugees, and other refugee and human rights? - Dinsel, Ann-Kristin Marie (Department of Public Law, 2025)
The number of people forcibly displaced worldwide is at an all-time high and will continue to rise in the foreseeable future. The United Kingdom (UK) has been striving to deter asylum seekers from coming to its territory. An example of this is the asylum partnership between the UK and Rwanda, signed in April 2022. Under this agreement, asylum seekers are forcibly relocated from the UK to Rwanda for the processing of their asylum claim without any possibility of returning to the UK. This agreement supposedly aims at responsibility-sharing and the promotion of better protection of asylum seekers. However, the UK has extensive resources and highly developed capabilities for processing asylum claims, whereas Rwanda struggles to meet the basic needs of its own population, and its asylum system is still developing. Therefore, this thesis sets out to investigate the compliance of the asylum partnership with international law. As many legal questions arise in this context, this thesis can only focus on some of them. Through an assessment of the applicable laws, both internationally and regionally, as well as by examining secondary sources, three main violations of international refugee and human rights law are identified, namely violations of the principle of nonrefoulement, the prohibition of the non-penalization of illegal entry by refugees, and other refugee and human rights obligations of the UK towards asylum seekers